An assessment of the evidence for antibacterial activity of stinging nettle (Urtica dioica) extracts. Issue 3 (24th March 2022) - Harrison, Freya; Furner-Pardoe, Jessica; Connelly, Erin
Abstract : Stinging nettles ( Urtica spp.) have been used in a diverse range of traditional and historical medicines from around the world for the treatment of skin diseases, wounds, urinary disorders, respiratory diseases, bone and joint pain, anaemia and other circulatory problems, as well as in cosmetic preparations for skin and haircare. As part of an interdisciplinary exploration of nettle-based remedies, we performed a systematic review of published evidence for the antimicrobial activity of Urtica spp. extracts against bacteria and fungi that commonly cause skin, soft tissue and respiratory infections. We focussed on studies in which minimum inhibitory concentration (MIC) assays of U. dioica were conducted on the common bacterial opportunistic pathogens Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae and Staphylococcus aureus . No studies used fresh leaves (all were dried prior to use), and no studies prepared nettles in weak acid (corresponding to vinegar) or in fats/oils, which are common combinations in historical and traditional preparations. We addressed this gap by conducting new antibacterial tests of extracts of fresh U. dioica leaves prepared in vinegar, butter or olive oil against P. aeruginosa and S. aureus . Our systematic review and additional experimental data leads us to conclude that there is no strong evidence for nettles containing molecules with clinically useful antimicrobial activity. It seems most likely that the utility of nettles in traditional topical preparations for wounds may simply be as a 'safe' absorbent medium for keeping antibacterial (vinegar) or emollient (oils) ingredients at the treatment site.